Vračilo preveč izplačanih plač - Lubinič, Marjana (Delavci in delodajalci, 2017)
The paper presents the case-law of the Supreme Court regarding the regulations of salaries in the public sector relating to prohibition of acknowledging greater rights for civil servants as those defined by the law, regulations and other acts issued on the basis thereof, or the respective collective agreement. The Supreme Court has dealt with the issues initiated by the lawsuits of the civil servants and also their employers. The first were concerned with the right of the employers to (unilaterally) intervene into the rights already recognised to the workers, and the second, on the duty of civil servants to return overpaid remuneration.
Keywords: javni uslužbenci; plače; pogodba o zaposlitvi; pravna ureditev; reševanje; sodna praksa; spori; vrhovna sodišča